Effect of heavy metals mixture on the growth and physiology of Tetraselmis sp.: Applications to lipid production and bioremediation. (September 2022) - Dammak, Mouna; Ben Hlima, Hajer; Tounsi, Latifa; Michaud, Philippe; Fendri, Imen; Abdelkafi, Slim
Graphical abstract: Highlights: Mixture Design was used to model the effect of metal ions on Tetraselmis sp. strain. Tetraselmis sp. was identified as an outstanding Ni, Cr and Co accumulator. The binary mixture Ni (54.45 %) and Cr (45.45 %) allowed highest metal removal (91%) FTIR analysis showed the presence of new functional groups for metal biosorption. Abstract: Phycoremediation of heavy metals from contaminated waters by oleaginous microalgae is an eco-friendly and emerging trend. Different concentrations of toxic metals such as nickel (Ni), chromium (Cr) and cobalt (Co) were added in Tetraselmis sp. culture media. Mixture Design was used to model the effect of these metals on cell growth, lipid production and heavy metals removal. Tetraselmis sp. was identified as an outstanding Ni, Cr and Co accumulator with bioconcentration factors of 675.17, 584.9 and 169.81 within binary mixtures (Ni × Cr), (Cr × Co) and (Cr × Co) at 6 mg/L, respectively. Optimization studies showed that the highest cell growth (9.22 × 10 5 cells/mL), lipid content (31% Dry Weight) and metals removal (91%) were obtained with the optimum binary mixture Ni (54.45 %) and Cr (45.45 %). This work presents interesting results revealing the potential of Tetraselmis sp. for nickel removal up to 97 % combined to its potential for biodiesel production.